GED - a generalised syntax editor : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Computer Science at Massey University - Moretti, Giovanni Serafino (Massey University, 1984)
This thesis traces the development of a full-screen syntax-directed editor - a type of editor that operates on a program in terms of its syntactic tree structure instead of its sequential character representation. The editor is table-driven, reading as input an extended BNF syntax of the target language. It can therefore be used for any language whose syntax can be defined in EBNF. Print formatting information can be included with the syntactic definition to enable programs to be pretty-printed when they are displayed. The user is presented with a pretty-printed skeletal outline of a program with the currently selected construct highlighted and all required syntactic items provided by the editor. Any constructs with alternatives, such as "", which occurs in many languages, are initially denoted by a placeholder in the form of a non-terminal name (i.e. "") which is expanded when the user indicates which alternative is wanted. All symbols entered by the user are parsed immediately and any erroneous symbols rejected, making it impossible to create a syntactically incorrect program. The editor cannot detect semantic errors as no semantic information is available from the EBNF syntax. However the first use of all identifiers is flagged by the editor as an aid to the detection of undeclared identifiers. A "help" area at the bottom of the screen continuously displays a list of the correct next symbols and the syntactic definition of the currently selected program construct. This display, together with a multi-level "undo" command and the provision of a skeletal program by the editor, provides a way of exploring the various constructs in a programming language, while ensuring the syntactic correctness of the resultant program.
Keywords: Programming languages (Electronic computers); Syntax